Exploring Understanding of Sports Injuries Among Beginning Athletes: A Study of Students - Arief Ibnu Haryanto; Ucok Hasian Refiater; Safri Irawan; Meri Haryani; Mohamad Daulima; Nurkhoiroh Nurkhoiroh; Husain I. Pakiun Pakiun (JUMORA: Jurnal Moderasi Olahraga, 2025)
The urgency of this research stems from the fact that even professional athletes still have a moderate level of knowledge regarding sports injuries. What about novice athletes who have only recently entered the world of athletics? This is a significant question that must be answered with evidence from academic research. This study aims to identify and analyze the level of understanding of sports injuries among novice track and field athletes at Gorontalo State University. Using a descriptive survey method, the study involved 24 students who had participated in basic athletic training for at least two months. The instrument used in this study has been proven valid with an r table value of 0.514 and a significance level of 5% and a reliability of 0.922 consisting of 33 questions. The data analysis technique is descriptive statistics using SPSS version 25. After the descriptive data is obtained, it is categorized using the Five Scale Conversion (KSL) formula. The results indicate that athletes' understanding of sports injuries is generally moderate, with most having a sufficient understanding of the types of injuries. However, knowledge regarding injury management and prevention remains low. Based on descriptive statistics, most participants had a poor understanding of injury prevention measures. A deeper understanding of sports injuries, management, and prevention is crucial for reducing injury risk and improving athlete performance. This study suggests the need for better education regarding sports injuries to optimize the safety and effectiveness of athletic training